Experimental Study of the Effect of Thickener on the Film Thickness in the Contacts of a Grease-Lubricated Ball Bearing at Low Speed - Okál, Michal; Košťál, David; Osara, Jude A.; Lugt, Piet; Křupka, Ivan; Hartl, Martin (Taylor & Francis Group, LLC., 2025)
The level of starvation in axially loaded grease lubricated ball bearings can be well described by the product of the base oil viscosity, the half contact width and the rotational speed (gbu). This paper highlights the effect of the thickener as another parameter for estimating the film thickness in a ball bearing. Film thickness measurements were done with an optical simulator of the ballon- disc configuration and a real ball bearing using the capacitance method. Three greases with the same base oil but different thickener types were selected for the experiments. Two greases followed the gbu model but the grease with alicyclic di-urea thickener produced a higher thickness than the model prediction, which is most likely caused by the formation of residual layers on the contact surfaces. The layer formation occurs in the first few hours of operation reaching a thickness of about 500–550 nm. Other greases also form layers, but they are comparable to prior observations, and they follow the model. The evolution of the normalized film thickness versus gbu in the case of alicyclic-di urea grease shows the same trend as the other grease types but with overall higher values.

The level of starvation in axially loaded grease lubricated ball bearings can be well described by the product of the base oil viscosity, the half contact width and the rotational speed (gbu). This paper highlights the effect of the thickener as another parameter for estimating the film thickness in a ball bearing. Film thickness measurements were done with an optical simulator of the ballon- disc configuration and a real ball bearing using the capacitance method. Three greases with the same base oil but different thickener types were selected for the experiments. Two greases followed the gbu model but the grease with alicyclic di-urea thickener produced a higher thickness than the model prediction, which is most likely caused by the formation of residual layers on the contact surfaces. The layer formation occurs in the first few hours of operation reaching a thickness of about 500–550 nm. Other greases also form layers, but they are comparable to prior observations, and they follow the model. The evolution of the normalized film thickness versus gbu in the case of alicyclic-di urea grease shows the same trend as the other grease types but with overall higher values.
Experimental Study of the Effect of Thickener on the Film Thickness in the Contacts of a Grease-Lubricated Ball Bearing at Low Speed
Keywords: EHL: grease; thickener; ball bearing; EHL: grease; thickener; ball bearing